Education and Employment: Two Ongoing Challenges - Roberto Cipriani (Pensa MultiMedia, 2022)
The relationship between education and employment is immediate. From one descends the other. Italian political events have witnessed the contribution of ministers who, coming from the university world, have tried to give an accentuated impulse to reforms in the field of training. But the follow-up has not been entirely happy, when there have been other ministerial leaders. Scientific research is an obligatory step in any educational pathway. And its results must be duly and widely disseminated at all levels, in an accessible, clear and open form to every possible user. Another fairly close link is that between work and the economy, with implications that cannot fail to take into account the time factor and the dominant presence of IT tools. Not to mention the necessary extension of the discourse to perspectives of an international nature, not detached from roots of a localist nature. Which finds an extraordinary opportunity for 'glocal' (global and local) convergence in the PNRR.